CCR8 Signaling via CCL1 Regulates Responses of Intestinal IFN-γ Producing Innate Lymphoid CelIs and Protects From Experimental Colitis - Kang, Le; Schmalzl, Angelika; Leupold, Tamara; Gonzalez-Acera, Miguel; Atreya, Raja; Neurath, Markus; Becker, Christoph; Wirtz, Stefan (Frontiers in Immunology, 2021)
A diverse spectrum of immune cells populates the intestinal mucosa reflecting the continuous stimulation by luminal antigens. In lesions of patients with inflammatory bowel disease, an aberrant inflammatory process is characterized by a very prominent infiltrate of activated immune cells producing cytokines and chemokines. These mediators perpetuate intestinal inflammation or may contribute to mucosal protection depending on the cellular context. In order to further characterize this complex immune cell network in intestinal inflammation, we investigated the contribution of the chemokine receptor CCR8 to development of colitis using a mouse model of experimental inflammation. We found that CCR8−/− mice compared to wildtype controls developed strong weight loss accompanied by increased histological and endoscopic signs of mucosal damage. Further experiments revealed that this gut protective function of CCR8 seems to be selectively mediated by the chemotactic ligand CCL1, which was particularly produced by intestinal macrophages during colitis. Moreover, we newly identified CCR8 expression on a subgroup of intestinal innate lymphoid cells producing IFN-γ and linked a functional CCL1/CCR8 axis with their abundance in the gut. Our data therefore suggest that this pathway supports tissue-specific ILC functions important for intestinal homeostasis. Modulation of this regulatory circuit may represent a new strategy to treat inflammatory bowel disease in humans.
CRIS-Team Scopus Importer:2021-03-05
Keywords: CCR8; chemokines; cytokines; inflammatory bowel disease; innate immunity; innate lymphoid cell

ILCs—Crucial Players in Enteric Infectious Diseases - Leupold, Tamara; Wirtz, Stefan (International Journal of Molecular Sciences, 2022)
Research of the last decade has remarkably increased our understanding of innate lymphoid cells (ILCs). ILCs, in analogy to T helper (Th) cells and their cytokine and transcription factor profile, are categorized into three distinct populations: ILC1s express the transcription factor T-bet and secrete IFNγ, ILC2s depend on the expression of GATA-3 and release IL-5 and IL-13, and ILC3s express RORγt and secrete IL-17 and IL-22. Noteworthy, ILCs maintain a level of plasticity, depending on exposed cytokines and environmental stimuli. Furthermore, ILCs are tissue resident cells primarily localized at common entry points for pathogens such as the gut-associated lymphoid tissue (GALT). They have the unique capacity to initiate rapid responses against pathogens, provoked by changes of the cytokine profile of the respective tissue. Moreover, they regulate tissue inflammation and homeostasis. In case of intracellular pathogens entering the mucosal tissue, ILC1s respond by secreting cytokines (e.g., IFNγ) to limit the pathogen spread. Upon infection with helminths, intestinal epithelial cells produce alarmins (e.g., IL-25) and activate ILC2s to secrete IL-13, which induces differentiation of intestinal stem cells into tuft and goblet cells, important for parasite expulsion. Additionally, during bacterial infection ILC3-derived IL-22 is required for bacterial clearance by regulating antimicrobial gene expression in epithelial cells. Thus, ILCs can limit infectious diseases via secretion of inflammatory mediators and interaction with other cell types. In this review, we will address the role of ILCs during enteric infectious diseases.
CRIS-Team Scopus Importer:2022-12-09
Keywords: crosstalk between ILCs and other immune cells; cytokine responses; enteric infections; ILC plasticity; innate lymphoid cells (ILCs); mucosal immunity; tissue homeostasis and ILCs

Interferon regulatory factor 1 (IRF-1) promotes intestinal group 3 innate lymphoid responses during Citrobacter rodentium infection - Schmalzl, Angelika; Leupold, Tamara; Kreiß, Lucas; Waldner, Maximilian; Schürmann, Sebastian; Neurath, Markus; Becker, Christoph; Wirtz, Stefan (Nature Communications, 2022)
Group 3 innate lymphoid cells (ILC3s) are crucial mediators of immunity and epithelial barrier function during immune responses against extracellular bacteria. Here, we identify Interferon regulatory factor 1 (IRF-1), a transcription factor previously associated with type 1 immunity, as an essential regulator of intestinal ILC3 accumulation and effector cytokine production. We demonstrate that IRF-1 is upregulated in the context of infection with the enteropathogen Citrobacter rodentium and that its presence is central for anatomical containment and prevention of pathogen dissemination. We furthermore show that IRF-1 is required in order for intestinal ILC3s to produce large amounts of the protective effector cytokine IL-22 early in the course of infection. On a molecular level, our data indicate that IRF-1 controls ILC3 numbers and their activation by direct transcriptional regulation of the IL-12Rβ1 chain, thereby allowing ILCs to physiologically respond to IL-23 stimulation.
CRIS-Team Scopus Importer:2022-10-14

RNAi-mediated gene knockdown of progesterone 5β-reductases in Digitalis lanata reduces 5β-cardenolide content - Klein, Jan; Horn, Elisa; Ernst, Mona; Leykauf, Tim; Leupold, Tamara; Dorfner, Maja; Wolf, Laura-Sophie; Ignatova, Anastasiia; Kreis, Wolfgang; Munkert, Jennifer (Plant Cell Reports, 2021)
Key message: Studying RNAi-mediated DlP5βR1 and DlP5βR2 knockdown shoot culture lines of Digitalis lanata, we here provide direct evidence for the participation of PRISEs (progesterone 5β-reductase/iridoid synthase-like enzymes) in 5β-cardenolide formation. Abstract: Progesterone 5β-reductases (P5βR) are assumed to catalyze the reduction of progesterone to 5β-pregnane-3,20-dione, which is a crucial step in the biosynthesis of the 5β-cardenolides. P5βRs are encoded by VEP1-like genes occurring ubiquitously in embryophytes. P5βRs are substrate-promiscuous enone-1,4-reductases recently termed PRISEs (progesterone 5β-reductase/iridoid synthase-like enzymes). Two PRISE genes, termed DlP5βR1 (AY585867.1) and DlP5βR2 (HM210089.1) were isolated from Digitalis lanata. To give experimental evidence for the participation of PRISEs in 5β-cardenolide formation, we here established several RNAi-mediated DlP5βR1 and DlP5βR2 knockdown shoot culture lines of D. lanata. Cardenolide contents were lower in D. lanata P5βR-RNAi lines than in wild-type shoots. We considered that the gene knockdowns may have had pleiotropic effects such as an increase in glutathione (GSH) which is known to inhibit cardenolide formation. GSH levels and expression of glutathione reductase (GR) were measured. Both were higher in the Dl P5βR-RNAi lines than in the wild-type shoots. Cardenolide biosynthesis was restored by buthionine sulfoximine (BSO) treatment in Dl P5βR2-RNAi lines but not in Dl P5βR1-RNAi lines. Since progesterone is a precursor of cardenolides but can also act as a reactive electrophile species (RES), we here discriminated between these by comparing the effects of progesterone and methyl vinyl ketone, a small RES but not a precursor of cardenolides. To the best of our knowledge, we here demonstrated for the first time that P5βR1 is involved in cardenolide formation. We also provide further evidence that PRISEs are also important for plants dealing with stress by detoxifying reactive electrophile species (RES).
CRIS-Team Scopus Importer:2021-07-02
Keywords: Cardenolide biosynthesis; Digitalis lanata; Glutathione; Progesterone 5β-reductases (P5βR); Reactive electrophile species; RNAi-mediated knockdown